Anti-hyperalgesic Activity of Ficus Deltoidea in an Animal Model of Migraine - Safuraa Salihan; Mohamad Aris Mohd Moklas; Mohamed Hanief bin Khalid; Samaila Musa Chiromaa; Mohd Roslan Sulaiman; Mohamad Taufik Hidayat Baharuldin (CSIR-National Institute of Science Communication a, 2024)
Indexed by WOS/ Scopus